Q Quality Of Work Life, Kaizen Culture, Job Satisfaction, and Organizational Commitment: QUALITY OF WORK LIFE, KAIZEN CULTURE, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT - Farida Yuliaty (Khazanah Intelektual, 2021)
The purposes of this research are to know (1) the influence of quality of work life to a job satisfaction (2) the influence of kaizen culture to a job satisfaction (3) the influence of quality of work life to organization commitment (4) the influence of kaizen culture to organization commitment (5) the influence of job satisfaction to organization commitment (6) the influence of quality of work life and kaizen culture to a job satisfaction and the impact to organization commitment in HRD Directory of PT Biofarma. The data collection method is done through questionnaire that distributed to employees of HRD Directory of PT Biofarma (Persero) that 40 respondent were taken. With saturated sampling techniques, datas that taken then processed by using data analysis. Data analysis in this research is qualititave data analysis, descriptive and verificative. This analysis is involves reliability test, statistic test through Ttest, Ftest, also the coefficient of R2 determination, classical assumption test and path analysis. Based on the analysis of the research, therefore can be concluded that (1) quality of work life have negative effect and not significant to job satisfaction, (2) kaizen culture have positive effect and significant to job satisfaction, (3) quality of work life have negative effect and not significant to organization commitment, (4) kaizen culture have negative effect and not significant to organization commitment, (5) job satisfaction have positive effect and significant to organization commitment (6) quality of work life and kaizen culture have positive effect and significant to organization commitment through the job satisfaction.